Spinal Cord Involvement in Pediatric-Onset Metabolic Disorders With Mendelian and Mitochondrial Inheritance - Tabarki, Brahim; Hakami, Wejdan; Alkhuraish, Nader; Tlili-Graies, Kalthoum; Alfadhel, Majid (Frontiers in Pediatrics, 2021)
Previous reviews have described the features of brain involvement in pediatric-onset metabolic disorders with Mendelian and mitochondrial inheritance, but only a few have focused on spinal cord abnormalities. An increasing number of metabolic disorders with Mendelian and mitochondrial inheritance in children with predominant spinal cord involvement has been recognized. Spinal cord involvement may be isolated or may occur more frequently with brain involvement. Timely diagnosis and occasional genetic counseling are needed for timely therapy. Therefore, clinicians must be aware of the clinical, laboratory, and radiographic features of these disorders. In this review, we describe pediatric-onset metabolic disorders with Mendelian and mitochondrial inheritance and predominant spinal cord involvement. Furthermore, we provide an overview of these conditions, including background information and examples that require rapid identification, focusing on treatable conditions; that would be catastrophic if they are not recognized.